Embedding Vocabulary Instruction Into the Art Experience. (3rd June 2016) - LaBrocca, RoseAnn; Morrow, Lesley Mandel
Abstract: The purpose of this article is to describe how an elementary art specialist scaffolded learning of specific academic vocabulary during a unit on how to create hollow clay ceramic sculptures. Although much has been written recently on how elementary teachers might better teach academic vocabulary in reading and language arts contexts as well as in social studies, math, and science, addressing methods to teach academic vocabulary in the arts has been virtually ignored (Beck, McKeown, & Kucan, 2002; Blachowicz, Fisher, Ogle, & Watts‐Taffe, 2013). The article discusses (a) research, theory, and policy issues that support this initiative; (b) details of the sculpture‐related vocabulary and reading activities enacted in 14 art periods with third‐grade children; and (c) extensions and elaborations of this approach for other elementary educational contexts.